Transitions Asia: Managing Across Cultures - CHUA, Roy (Institutional Knowledge at Singapore Management University, 2013)
The director of an interim executive search firm, Chee Lung Tham, faced a clash of culture and management styles when his mainland Chinese client threatened to fire the American interim manager that Tham had assigned. The client, Wong Lung, ran a family-owned garment manufacturing business along with his younger brother, as well as his two overseas-educated children. While Wong needed the American manager's technology expertise, his own brother and his team of middle managers were showing resistance to the new changes. Meanwhile, the American manager found himself caught in the web of family and company politics, and completing his assignment without the cooperation of the middle management was impossible. How should Tham approach the conflict and bring all sides into a productive working relationship?